Differential expression of TLR3 and TLR4 in keratocystic odontogenic tumor (KCOT): A comparative immunohistochemical study in primary, recurrent, and nevoid basal cell carcinoma syndrome (NBCCS)–associated lesions. Issue 6 (July 2015) - Leonardi, R.; Perrotta, R.E.; Crimi, S.; Matthews, J.B.; Barbato, E.; dos Santos, J.N.; Rusu, M.; Bufo, P.; Bucci, P.; Pannone, G.
Abstract Background Toll-like receptors (TLRs) play an essential role in the activation of innate immunity and they can promote cancer cell survival and tumor progression. It has been claimed that TLRs can somehow predict the clinical behavior in oral squamous cell carcinoma (OSCCs). Aim To elucidate the molecular basis underlying keratocystic odontogenic tumor (KOCTs) aggressive behavior and recurrence we carried out this immunohistochemical study on TLR3 and TLR4 expression in sporadic primary KCOTs (sp-KCOTs), sporadic recurrent KCOTs (sp-KCOTs), and NBCCS-associated KCOTs (NBCCS-KCOTs). Method 40 cases of KOCTs removed from 23 men and 17 women were the sample. Paraffin-embedded blocks were processed for immunohistochemistry. Sections were incubated with TLR3 and TLR4 antibodies and immunoreactivity evaluated on a semi-quantitative score. Results Both TLR3 and TLR4 were expressed in KCOTs epithelium, although with a different extent. TLR3 was not expressed in sp-KCOTs and sr-KCOTs, but it showed a faint staining in NBCCS-KCOTs. On the other hand, both cytoplasmic and nuclear staining for TLR4 was detected in all the 3 types of lesions; however being significantly more expressed in sr-KCOT and NBCCS-KCOTs (p < 0.0001). Our results, demonstrated an association between TLR4, but not TLR3 expression to recurrence behavior of KCOTs. In fact, TLR4 was up-regulated in sr-KCOTs and NBCCS-KCOTs but not in sp-KCOTs. Conclusions According these findings it seems conceivable to assume that the up-regulation of TLR4 in some KCOTs can be correlated somehow to their tendency recurrence.